PRECEDENT PHENOMENA: STRUCTURE AND FUNCTIONS (Web of Teachers: Inderscience Research, 2024)
The article discusses the issue of defining and classifying precedent phenomena from the standpoint of an integrated approach. On the basis of the analysis, the definition and main and additional features of precedent phenomena are given, as well as the hierarchy of precedent phenomena is built.